Investigation of Reaction Dynamics of Methane Reforming on Nickel Clusters Using Molecular Dynamics Simulations - Arifin, Rizal; Muzakki, Fikrun Najib; Winardi, Yoyok; Widaningrum, Ida; Zulkarnain, Zulkarnain; Abdurrouf, Abdurrouf; Johari, Norhasnidawani; Lee, Vannajan Sanghiran; Darminto, Darminto (Journal of Engineering and Technological Sciences, 2025)
This study employed molecular dynamics simulations utilizing the ReaxFF force field to elucidate the mechanisms underlying methane decomposition and hydrogen generation on nickel clusters (Ni37, Ni55, and Ni80). The transformation of methane into valuable products, including carbon species and hydrogen molecules, is of considerable significance owing to the abundance of methane and its potential role as an atmospheric pollutant. The findings suggest that Ni37 clusters had the highest initial reactivity, although they deactivated swiftly; conversely, Ni55 and Ni80 exhibited more consistent reaction rates. The highest efficiency of hydrogen production per unit surface area was displayed by Ni55 clusters within 100,000 fs, demonstrating a balance between reactivity and stability. Methane dissociation on the Ni55 clusters occurred in multiple stages. Two distinct mechanisms for hydrogen formation were identified: simultaneous dissociation from methane and migration and the combination of hydrogen atoms on the cluster surface. Ni55 showed a substantially lower activation energy for methane dissociation at 0.5 eV than bulk nickel, suggesting a higher degree of reactivity. Conversely, the activation energy for hydrogen formation was 1.1 eV. These results highlight the potential of the Ni55 clusters as effective catalysts for hydrogen production and methane conversion